+0  
 
0
380
3
avatar

Hallo!

Ich muss das hier berechnen und komme einfach nicht weiter...

(-(4r/3pi)-r)*(pi/2*r^2)

 14.01.2017

Beste Antwort 

 #1
avatar+8238 
+5

(-(4r/3pi)-r)*(pi/2)*r^2

 

\(\large (-\frac{4r}{3\pi}-r)\times\frac{\pi}{2}r^2\)

 

\(\large =-\frac{4\pi r^3}{3\pi}-\frac{\pi r^3}{2}\)

 

\(\large=\frac{8r^3-3\pi r^3}{6}\)

 

\(\large=r^3(\frac{8-3\pi}{6})\)

 

\(\large=-1,0471975512 \ r^3\)

 

laugh   !

 14.01.2017
 #1
avatar+8238 
+5
Beste Antwort

(-(4r/3pi)-r)*(pi/2)*r^2

 

\(\large (-\frac{4r}{3\pi}-r)\times\frac{\pi}{2}r^2\)

 

\(\large =-\frac{4\pi r^3}{3\pi}-\frac{\pi r^3}{2}\)

 

\(\large=\frac{8r^3-3\pi r^3}{6}\)

 

\(\large=r^3(\frac{8-3\pi}{6})\)

 

\(\large=-1,0471975512 \ r^3\)

 

laugh   !

asinus 14.01.2017
 #2
avatar+100826 
0

OR

 

\(((\frac{-4r}{3}\pi)-r)*(\frac{\pi}{2}*r^2)\\ =(\frac{-4r\pi-3r}{3})*(\frac{\pi r^2}{2})\\ =\frac{1}{6}(-4\pi r-3r)(\pi r^2)\\ =\frac{\pi r^3}{6}(-4\pi -3)\\ =\frac{-\pi r^3}{6}(4\pi +3)\\ \)

.
 15.01.2017
 #3
avatar+8238 
+5

Auch richtig. Setzt doch Klammern Leute!

asinus  15.01.2017

9 Benutzer online